Awake proning in patients with COVID‐19‐related hypoxemic acute respiratory failure: A rapid practice guideline. Issue 5 (9th February 2023) - Myatra, Sheila Nainan; Alhazzani, Waleed; Belley‐Cote, Emilie; Møller, Morten Hylander; Arabi, Yaseen M.; Chawla, Rajesh; Chew, Michelle S.; Einav, Sharon; Ergan, Begum; Kjær, Maj‐Brit Nørregaard; McGloughlin, Steve; Nasa, Prashant; et al.
Abstract: This rapid practice guideline provides evidence‐based recommendations for the use of awake proning in adult patients with acute hypoxemic respiratory failure due to COVID‐19. The panel included 20 experts from 12 countries, including one patient representative, and used a strict conflict of interest policy for potential financial and intellectual conflicts of interest. Methodological support was provided by the guidelines in intensive care, development, and evaluation (GUIDE) group. Based on an updated systematic review, and the grading of recommendations, assessment, development, and evaluation (GRADE) method we evaluated the certainty of evidence and developed recommendations using the Evidence‐to‐Decision framework. We conducted an electronic vote, requiring >80% agreement amongst the panel for a recommendation to be adopted. The panel made a strong recommendation for a trial of awake proning in adult patients with COVID‐19 related hypoxemic acute respiratory failure who are not invasively ventilated. Awake proning appears to reduce the risk of tracheal intubation, although it may not reduce mortality. The panel judged that most patients would want a trial of awake proning, although this may not be feasible in some patients and some patients may not tolerate it. However, given the high risk of clinical deterioration amongst these patients, awake proning should be conducted in an area where patients can be monitored by staff experienced in rapidly detecting and managing clinical deterioration. This RPG panel recommends a trial of awake prone positioning in patients with acute hypoxemic respiratory failure due to COVID‐19.